A VR/AR Environment for Multi-User Liver Anatomy Education - Schott, Danny; Saalfeld, Patrick; Schmidt, Gerd; Joeres, Fabian; Boedecker, Christian; Huettl, Florentine; Lang, Hauke; Huber, Tobias; Preim, Bernhard; Hansen, Christian (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2021)
We present a Virtual and Augmented Reality multi-user prototype of a learning environment for liver anatomy education. Our system supports various training scenarios ranging from small learning groups to classroom-size education, where students and teachers can participate in virtual reality, augmented reality, or via desktop PCs. In an iterative development process with surgeons and teachers, a virtual organ library was created. Nineteen liver data sets were used comprising 3D surface models, 2D image data, pathology information, diagnosis and treatment decisions. These data sets can interactively be sorted and investigated individually regarding their volumetric and meta information. The three participation modes were evaluated within a user study with surgery lecturers (5) and medical students (5). We assessed the usability and presence using questionnaires. Additionally, we collected qualitative data with semistructured interviews. A total of 435 individual statements were recorded and summarized to 49 statements. The results show that our prototype is usable, induces presence, and potentially support the teaching of liver anatomy and surgery in the future.